2017
DOI: 10.1371/journal.pone.0189046
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of IDF, ATPIII and CDS in the diagnosis of metabolic syndrome among adult inhabitants in Jiangxi Province, China

Abstract: BackgroundCurrently, the prevalence of metabolic syndrome (MS) has attracted widespread public attention. However, there is a war regarding the applicability of the diagnosis in different populations regarding the distinct criteria for the diagnosis of MS. Data about the prevalence rate of MS and its components in Jiangxi Province are limited. Thus, our goals were to compare the consistency rates and applicability of three criteria, i.e., those of the International Diabetes Federation (IDF), the National Chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
5
12
0
Order By: Relevance
“…In the criterion of CDS, the prevalence of MetS in male was higher than that in female, while the male was lower than female under other criteria, which was consistent with the study of Wanghong Xu 20 . The components of highest proportions were blood pressure and waist circumference, which was similar to the result of Jiangxi province of China 21 . Based on these analyses, in Henan rural areas, we could know that the prevalence of MetS maintained a high level, while the blood pressure and waist circumference would be the important aspects to prevent MetS.…”
Section: Discussionsupporting
confidence: 81%
“…In the criterion of CDS, the prevalence of MetS in male was higher than that in female, while the male was lower than female under other criteria, which was consistent with the study of Wanghong Xu 20 . The components of highest proportions were blood pressure and waist circumference, which was similar to the result of Jiangxi province of China 21 . Based on these analyses, in Henan rural areas, we could know that the prevalence of MetS maintained a high level, while the blood pressure and waist circumference would be the important aspects to prevent MetS.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, low education level and the menopausal state could be independent associated factors for MS. MS increases the risk of T2DM, CVD and cancer in the general population, resulting in an enormous economic burden for the society [1,5]. MS prevalence were 19.85 and 9.95% in 2013 in Jiangxi province based on IDF and CDS criteria, respectively, as reported by Cheng et al [22].. After 2 years, a significant increase was observed in this survey. This terrible phenomenon suggests that effective prevention measures should be taken immediately.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, we found a high prevalence of MS of 20.1% among 26836 participants in Yuhuan County, a coastal area located in developed East China, which was similar to previous studies ranging from 22.0-25.3%, and a higher prevalence for females was observed, which was consistent with previous studies [14,25,26]. Compared with the Northwest or other developing areas in China, MS was more prevalent in East China [27,28].…”
Section: Discussionsupporting
confidence: 91%